Evaluation of hydrolytic enzyme activities from digestive fluids of Anthonomus grandis (Coleoptera: Curculionidae) - Ben Guerrero, Emiliano; Salvador, Ricardo; Talia, Paola Mónica (Wiley, 2020)
The cotton boll weevil, Anthonomus grandis, is a major pest of cotton crops in South America. In this work, partial biochemical characterizations of (hemi) cellulases and pectinases activities in the digestive system (head‐ and gut‐ extracts) of A. grandis were evaluated. Gut extract section from third instar larvae exhibited endoglucanase, xylanase, β‐glucosidase, and pectinase activities. The endoglucanase and xylanase activities were localized in the foregut, whereas β‐glucosidase activity was mainly detected in the hindgut. In addition, no difference in pectinase activity was observed across the gut sections. Thus, A. grandis digestive system is a potentially interesting reservoir for further lignocellulolytic enzymes research.